A public relations plan and programs for the University of the Philippines Diliman libraries - Palabrica, Cristina M.; Yang, Jackson V.; Santos, Herminia H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
Library public relations is currently being practiced and encouraged by libraries of all types in many countries throughout the world. It has greatly contributed to the enhancement of the library's image through action programs that aim to establish and maintain a good and cooperative relationship between the library and its diverse clients.
In the Philippines, the professionalization of librarianship has paved the way for professionals to make valuable contributions toward the further development of the profession. However, library public relations has not been fully explored because more effort is focused on the technical aspect as evident in the curricular requirements of library schools and even the training programs being offered by library organizations.
At the University of the Philippines Diliman campus, public relations work in any of the various unit libraries is not compulsory since the market is already considered captured in an academic library. This is because the setting requires extensive support for research, instruction and learning which is the main responsibility of the library.
This research study the current PR efforts of the UP Diliman libraries and design a PR plan and programs that focus on the various publics of an academic library. The University Librarian along with twenty-six (26) librarians were interviewed consisting of section heads from the Main Library and college librarians from the various units and colleges throughout the Diliman campus. The case study method was used in this research.
Results of the study reveal that there are no formal PR plan and/or programs being employed in any of the libraries within Diliman, including the Main Library primarily because it is not a priority. Also, the librarians still have to acquire more training and exposure to actual PR work. Anyway, the head librarians were all found to have interest in knowing more about library PR also for their own professional development.
Library public relations in UP Diliman is the efficient delivery of service backed by its collection, facilities and staff. Thus, the formation of 5 working committees namely: (1) Collection Development, (2) Staff training and Development, (3) Automation and Systems Development, (4) User Education and Services, and finally (5) Research & Publications. A library plan and programs were designed for each committee to address specific issues that are part of each committee's key area of concern.
This study recommends that the librarians undergo an extensive training on library PR with the help of professional PR practitioner. The PR expert can provide positive inputs to formulate policies and procedures concerning library PR. Lastly and more importantly, the expertise of a PR practitioner can provide substantial assistance in planning and execution of action programs for and of the Diliman libraries towards its promotion as a dynamic member of the academic community.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Public relations -- Philippines -- Diliman (Quezon City).; Libraries -- Public relations -- Philippines -- Diliman (Quezon City).